Low‐grade diffusely infiltrative tumour (LGDIT), SMARCB1‐mutant: A clinical and histopathological distinct entity showing epigenetic similarity with ATRT‐MYC. (18th February 2022) - Hasselblatt, Martin; Thomas, Christian; Federico, Aniello; Bens, Susanne; Hellström, Mats; Casar‐Borota, Olivera; Kordes, Uwe; Neumann, Julia E.; Dottermusch, Matthias; Rodriguez, Fausto J.; Lo, Andrea C.; Cheng, Sylvia; et al.
Abstract : Low‐grade diffusely infiltrative tumour (LGDIT), SMARCB1‐mutant, is a histopathological distinct low‐grade lesion encountered in older children and young adults that shows epigenetic similarity with ATRT‐MYC and has the potential for malignant progression.